Study of immuno-histochemical markers ER, PR and Her2/neu in ovarian neoplasms - Choudhary, Anjana; Pachori, Geeta; Mavaliya, Vivek; Pachori, Saroj (International Journal of Research in Medical Sciences, 2022)
Background: Among genital malignancies, ovarian cancer has the most increased mortality rate. ER, PR and HER2/neu expression levels depend on tumour histologic grade, stage of disease and age group. Aim of the study was to study the clinic-pathological parameters in ovarian tumours with reference to age, histologic type and grade and their correlation with ER, PR and HER2/neu status. Methods: The prospective study of 2 ½ years was conducted on 100 resected ovarian tumour specimens from June 2017 to December 2019 received in the department of pathology, JLN medical college, Ajmer. Sections were examined for presence of ovarian tumour, histological type, grade and for ER, PR and HER2/neu status, immunohistochemistry was done. Results: Out of 100 cases, 72 cases were benign, 03 cases were border-line and 25 cases were malignant. Serous tumors were most common among all epithelial tumors (61%). Malignant cases showed maximum positivity with ER, PR and HER2 as 61.76%, 68% and 100% respectively. ER, PR and HER2/neu positivity in serous epithelial tumors was 76.47%,84% and 90% and in mucinous tumors was 20.59%, 12% and 10% respectively. Majority of positive ER, PR and HER2/neu receptors was observed in age groups of >40 years as 64.71%, 64% and 85% respectively. ER, PR and HER2/neu positivity seen in higher grade and stage tumors as 76.19%, 76.47% and 70% in grade 3 and stage 3 tumors respectively. Conclusions: The higher expression of ER, PR and HER-2/Neu is associated with progression of invasive cancer, higher grade and stage of ovarian tumors, higher age group, and multiparty.